The Impact of Technical Competency Standards for Policy Analysts on the Quality of Public Policy Formulation in Indonesia - Risman Setiawan (Journal of Communication, Sustainability, and Empowerment, 2026)
This study is motivated by the phenomenon of low-quality public policies in Indonesia, characterized by a high rate of regulatory overlap and policy annulments by the Constitutional Court due to weaknesses in the formulation stage. The objective of this study is to conduct an in-depth analysis of the influence of technical competency standards for policy analysts on the quality of public policy formulation in Indonesia. The research method employed is a normative legal approach using both a statutory approach and a conceptual approach. The research results indicate that standardizing technical competencies based on Evidence-Informed Policymaking and mastery of big data literacy significantly enhances individual analytical capacity to produce accurate, evidence-based policy recommendations. These findings reveal a gap between current regulatory standards and the demands of complex analytical practices in the field, where strengthening technical competencies has proven to be a determining factor in reducing formulation errors. In conclusion, strengthening technical competency standards is a crucial pillar for the success of bureaucratic reform. The implications of these findings recommend the need for a reorientation of the training curriculum for policy analyst positions by the National Administrative Agency to be more adaptive to digital transformation, thereby ensuring higher-quality, accountable, and far-reaching public policy practices in Indonesia.